Modelling a domestic tourism destination: adapting the Regional Tourism Model to the Nord-Pas-de-Calais - Myriam Oumheta; Sylvain Petit (Via@)
Tourism is defined by demand, and visitors shape the product they consume. However, we observe a predominance of supply-oriented tourism diagnostic models in the literature. The literature on domestic tourism also remains sparse compared to scholarship focusing on international tourism. Therefore, we propose in this article to apply the Regional Tourism Model (MTR, Modèle de Tourisme Régional, Grandpré, 2009) to the Nord-Pas-de-Calais region. What makes this territory distinctive is that it has the highest level of proximity tourism – visitors from neighbouring countries (Great Britain, Belgium, Germany, the Netherlands) and residents of the Hauts-de-France region. However, we are introducing a major modification to the MTR by proposing a different construction methodology: Homogeneous Recreational Spaces (HRSs). We have identified six HRSs with their own distinctive landscape, heritage, and visitor perception. An HRS can therefore be supported by clearly differentiated tourism development strategies and tourism products.